Tubo-Ovarian Abscess Occurring 16 Years After Supracervical Hysterectomy - Toshimitsu Tohya; Toshihiro Yoshimura; Chikashi Onoda (Hindawi Limited, 2003)
Background: Supracervical hysterectomy is seldom performed and there are few reports of tubo-ovarian abscess (TOA) after supracervical hysterectomy.